Meningeal lymphatic-associated brain swelling in acute stroke - Rohan Mahesh Patil; Dong Bin Back; Gen Hamanaka; Rakhi Desai; Ayumi Hayakawa; Su Jing Chan; Bum Ju Ahn; Giuseppe Pignataro; Kazuhide Hayakawa; Elga Esposito (PLoS ONE, 2026)
Brain meninges contain lymphatic vessels that play roles in clearance of extracellular solute in the central nervous system. But, whether and how the system is involved in acute stroke remains to be fully explored. Here, we show the VEGF-C-Flt4 pathway involvement in brain swelling in acute phase of ischemic stroke in rats. We first confirmed that a prototypical lymphatic mediator VEGF-C was upregulated in brain endothelium and secreted into CSF. Concomitantly, VEGF-C receptor Flt4 was increased in the meninges but not in peri-infarct cortex. Next, we isolated lymphatic endothelial cells from rat meninges using LYVE-1 antibody-conjugated magnetic beads. An in vitro standard matrigel assay confirmed that isolated LYVE1 + cells increased ring-like structures by treatment with VEGF-C or conditioned media from injured brain endothelium subjected to oxygen-glucose deprivation, whereas immunodepletion of VEGF-C from endothelial media decreased the effect. Finally, blocking Flt4 tyrosine kinase in vivo suppressed the acute increase of lymphatic endothelial cells accompanied by reduction of brain swelling. Collectively, the proof-of-concept study suggests that the VEGF-C–Flt4 signaling pathway contributes to brain swelling during the acute phase of ischemic stroke by activating meningeal lymphatic endothelial cells. Targeting this pathway may offer a new approach to mitigate stroke-induced inflammation and edema.